Analysis of the Implementation of the Family Hope Program in an Effort to Reduce Poverty in Simandraolo Village, Gunungsitoli District, In 2023 - Glory Chris Muliana Telaumbanua; Jesslyn Elisandra Harefa; Amstrong Harefa; Berkat Iman Jaya Gea (Universitas Muhammadiyah Enrekang, 2023)
This research is motivated by problems caused by the implementation of the Family Hope Program (PKH) carried out in Simandraolo Village, Gunungsitoli District, Gunungsitoli City has not been implemented properly. This can be seen from several problems, namely: 1). There are still residents of Simandraolo Village who do not receive PKH who should be eligible to receive it. 2). There are families who do not have complete data. 3). There are still families who have not been data or verified data from the Social Service even though it is clear that the specific purpose of PKH is to reduce poverty. The research method used is a descriptive research method with a qualitative approach and with a total of 10 informants. The obstacles found include: 1). Some residents do not have complete data. 2). A small part has never been data by officers from the Social Service. 3). The process of collecting PKH assistance funds requires a distance from Simandraolo Village so that residents have to spend money on transportation. To overcome these various obstacles, the following efforts were made: 1). The Village Head and village officials work together with PKH Facilitators to recollect data if there are residents who have not received PKH who should be eligible to receive PKH. 2). For residents who have incomplete data, village officials facilitate to complete the data. 3). Village assistants or the Social Service always update data. 4). Village assistants routinely conduct home visits and PKH socialization activities. 5). As a community, they must provide original data to the Social Service and use PKH funds specifically for children's health and education.